Breast Cancer Awareness Among Nursing Students of Jinnah Hospital Lahore - Kanza Shehzadi, Amina Rafique, Ruqquia Rehman, Komal Liaqat, Sheeza Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer is a condition in which a mass of undifferentiated cells is formed as a result of an uncontrollable increase in the number of breast cells. The risk of breast cancer may be increased by physiological elements such as premature menarche, prolonged menstrual period, late age at first pregnancy, and low fertility. For every year that menopause is postponed, the risk of having breast cancer increases by 3%. Objective: To determine the Breast Cancer Awareness among nursing students of Jinnah Hospital Lahore Methodology: A descriptive cross-sectional study approach was used for this research. A sample size of 122 instances was calculated with a 95% confidence interval. The data was gathered using a random sample technique. Data was gathered from BSc Nursing students, Diploma students, LHV students, and BSC students. On a 20-point scale, knowledge about cancer in breast was evaluated. Results: The findings of study revealed that majority of student nurses 45 (36.8%) were less than 18 years and more than two-third, 67(54.9%) of participants were BSN students. The result shows that majority of the participants have average information, only 13.9% participants have poor knowledge about breast cancer. While 32% participants have good knowledge. Findings of study also revealed that knowledge about breast cancer is significantly associated with age and qualification of participants. Practical Implication: Therefore, there is a need to arrange the educational sessions and seminars on breast cancer to adequately inform about this illness. Conclusion: it is concluded that the participants had adequate knowledge of breast cancer and there is no association between knowledge of participants and residence. While age and qualification had significant association with knowledge of participants about breast cancer. Keywords: knowledge; Breast Cancer; Nursing Students; Breast Cancer Awareness; Cancer